Natrium Alginat sebagai Polimer Mukoadhesif terhadap Daya Lekat serta Pelepasan Granul Mukoadhesif Amoksisilin - Yudi Srifiana; Ari Widayanti; Nopriadi Nopriadi (Fakultas Farmasi Universitas Pancasila, 2019)
Mucoadhesive is a bioadhesive dosage form which forms a bond with mucous membranes. Mucoadhesive dosage forms stayed on mucous membranes in prolonged time so can increase bioavailability. This study intended to determine the effect of sodium alginate as bioadhesive polymer to mucoadhesive strength of granules. The granules prepared using amoxicillin as active agent and sodium alginate as bioadhesive polymer by wet granulation method. Granule evaluation are moisture content, particle size, wash off test using rat stomach and dissolution test. Test results of total recovery F1, F2, F3, F4, F5, 540 mg, 560 mg, 580 mg, 600 mg, 620 mg. Test results of flow rate 10,78-11,75 g/second, and angle of repose 33,50-35,15°, test of particle size distribution in the range of 1410-1680 µm, moisture content from 11.07 to 13.57%, wash off test of F1, F2, F3, F4 and F5 as consecutively 12.67, 14.00, 18.67, 26.00 and 33.33%. 2-way ANOVA test to % dissolution and wash-off test results sig. <0.05, so there is a significant difference between formulas. Based on the results showed that increasing concentration of sodium alginate increase mucoadhesive strength of granules but less able to resist of drug release, and the best formula is F3 that containing sodium alginate 580 mg.